Analysis of a gaussian process and feed-forward neural networks based filter for forecasting short rainfall time series - Rodriguez Rivero, C.; Pucheta, J.; Patiño, H.; Baumgartner, J.; Laboret, S.; Sauchelli, V. (2022)
Fil: Rodriguez Rivero, C. Universidad Nacional de Córdoba; Argentina.